Mapping the Intellectual Structure of Gamification Research in Education: A Bibliometric Perspective - Loso Judijanto (Westscience Press, 2026)
Due to the exponential growth of the number of gamification papers published in education, it becomes increasingly difficult to outline the field's intellectual structure and dynamics. To this end, this paper intends to map the intellectual structure and dynamics of gamification research in education through a bibliometric approach. The data were extracted from Scopus databases and analyzed with the help of VOSviewer with a focus on analyzing co-authorship networks, citations, and co-occurrences of keywords. According to the findings, the field has a clustered nature of author collaboration; some authors and institutions significantly contribute to the development of gamification knowledge in the sphere of education. Citation analysis showed a domination of specific institutions in the field such as Tampere University and University College Dublin. Keyword analysis proved a significant concentration of research on concepts such as gamification, students, motivation, teaching, learning which means that the researchers pay much attention to the improvement of educational practices and processes. At the same time, according to overlay visualization, the field is developing towards shifting the focus from purely technology-based studies to learning-centered ones. The study concludes that gamification research in education is a mature and interdisciplinary field with strong theoretical foundations, yet it still offers opportunities for broader collaboration, technological integration, and expansion into underrepresented regions. These findings provide valuable insights for researchers and practitioners in understanding current developments and guiding future research directions.